HUBUNGAN ANTARA BIMBINGAN SOSIAL DENGAN KEMAMPUAN BERKOMUNIKASI SISWA KELAS VIII SMP BABURROHMAH MOJOSARI - munawaroh, mas'ulil (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2020)
With the competency standard of education unit graduates from basic education units at the level of SMP / MTs / SMPLB / Package B, which among others are able to communicate and interact effectively and politely, while social guidance has an important role for individual students. Therefore it is important to know the relationship between social guidance and the ability to communicate in junior high school students in order to know the competency standards of graduates produced by the education unit. Formulation of the research problem, how is social guidance and communication skills of students of class VIII at SMP I Baburr Rohmah Mojosari in 2019, is there a relationship between social guidance and students 'communication skills and how big is the relationship of social guidance with students' communication skills. The hypothesis of this study is that there is a relationship between social guidance and the ability to communicate with students of class VIII SMPI Babur Rohmah Mojosari. The results of the study that social guidance in class VIII SMPI Babur Rohmah Mojosari is categorized as good at intervals of 35-44 (82.46%), and students' communication skills are in good category at intervals of 42-54 (64.91%). The result is that there is a relationship between social guidance and communication skills of students of class VIII SMPI Babur Rohmah Mojosari in 2018/2019, with the r pillar count (0.387) greater than r table (0.330) at a significant level Î± = 0.01. The magnitude of the relationship of social guidance with the ability to communicate with students by 14, 9769%, the rest 85.0231% is influenced by other factors. Keywords: Social guidance, communication skills.